Ghana’s economy-wide transformation: Past patterns and future prospects - Diao, Xinshen; Hazell, Peter B. R. (International Food Policy Research Institute, 2019)
Chapter 2 shows that the predominant source of labor productivity growth in Ghana has come from productivity increases within sectors, with the agricultural sector showing a particularly strong performance. Rodrik attributes this source of growth to what he calls “fundamental capabilities,” or the longer-term benefits from investments in better institutions, healthier and better educated workers, technologies, and more enabling policies. Another source of productivity growth arises from the movement of workers from low to higher productivity sectors, (e.g., from traditional agriculture to manufacturing). Rodrik calls this the gains from “structural change,” which result from changes in the relative importance of different sectors in national income and employment.